2018
DOI: 10.1007/s10126-018-9841-5
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive and Chloroplast Targeted Expression of Acetyl-CoA Carboxylase in Oleaginous Microalgae Elevates Fatty Acid Biosynthesis

Abstract: Photosynthetic microalgae are of burgeoning interest in the generation of commercial bioproducts. Microalgae accumulate high lipid content under adverse conditions, which in turn compromise their growth and hinder their commercial potential. Hence, it is necessary to engineer microalgae to mitigate elevated lipid accumulation and biomass. In this study, we identified acetyl-CoA carboxylase (ACCase) in oleaginous microalga Phaeodactylum tricornutum (PtACC2) and expressed constitutively in the chloroplast to dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…On the other hand, Rengel et al [1] isolated the ACC gene from Chlamydomonas reinhardtii and identified it at 1600 bp. and Li et al [31] reported the ACC gene from Phaeodactylum tricornutum at 1490 bp. In contrast, E. coli ACC consists of four subunits accA, accB, accC, and accD [32], which may lead to the visualization of three bands.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Rengel et al [1] isolated the ACC gene from Chlamydomonas reinhardtii and identified it at 1600 bp. and Li et al [31] reported the ACC gene from Phaeodactylum tricornutum at 1490 bp. In contrast, E. coli ACC consists of four subunits accA, accB, accC, and accD [32], which may lead to the visualization of three bands.…”
Section: Discussionmentioning
confidence: 99%
“…OPEN ACCESS promoters, the 2A signal peptide-based system for multi-cistronic expression of heterologous proteins, gene stacking techniques based on bidirectional promoters, the identification of resistance to multiple antibiotics, Cre recombinase-based marker recycling, and, last but not least, CRISPR-associated nucleases for precise genome editing (Box 1), are some recent developments that could be exploited for expressing a large number of heterologous proteins in microalgal strains [86][87][88][89][90][91][92]. We believe that the growing knowledge about efficient and transplantable CO 2 fixation pathways, together with state-of-the-art techniques for heterologous protein expression and for adaptive evolution, should be combined to develop microalgal strains with improved CO 2 fixation ability.…”
Section: Trends In Biotechnologymentioning
confidence: 99%
“…Saturated and mono-unsaturated C 14 -C 20 fatty acids from microalgae are exploited for renewable liquid biofuel production, while the engineering biosynthesis of long chain-polyunsaturated fatty acids (LC-PUFAs), important components of the human diet, might become a viable option in the market of high-value food additives [114]. Metabolic engineering reports for redirecting carbon fluxes toward fatty acid production in microalgae, included the up-regulation of key biosynthetic enzymes: (i) acetyl-CoA carboxylase, catalysing the first step for fatty acid biosynthesis, was successfully over-expressed in the chloroplast of P. tricornutum [115]; (ii) malonyl-CoA ACP transacylase enzyme, which catalyses the formation of malonyl-ACP, was over-expressed in both N. oceanica and Schizochytrium spp., resulting in 31% and 39.6% total lipid increase with respect to the control genotype, respectively [116,117]; (iii) acyl-ACP thioesterases (TE), involved in the last step of fatty acids biosynthesis, was heterologously expressed in different strains of microalgae [118,119]. In Dunaliella tertiolecta, a combinational expression platform involving plant lauric acid-TE (C12TE) and medium-chain fatty acid-specific ketoacyl-ACP synthase was recently engineered, and resulted in a significant increase in lauric acid (C12:0) and myristic acid (C14:0) accumulation [120].…”
Section: Engineering Of the Lipid Biosynthesis For Renewable Energiesmentioning
confidence: 99%